Toward structure-based drug design against the epidermal growth factor receptor (EGFR) - Haddad, Yazan; Remes, Marek; Adam, Vojtech; Heger, Zbynek (Drug discovery today, 2021)
Most of the available crystal structures of epidermal growth factor receptor (EGFR) kinase domain, bound to drug inhibitors, originated from ligand-based drug design studies. Here, we used variations in 110 crystal structures to assemble eight distinct families highlighting the C-helix orientation in the N-lobe of the EGFR kinase domain. The families shared similar mutational profiles and similarity in the ligand R-groups (chemical composition, geometry, and charge) facing the C-helix, mutation sites, and DFG domain. For structure-based drug design, we recommend a systematic decision-making process for choice of template, guided by appropriate pairwise fitting and clustering before the molecular docking step. Alternatively, the binding site shape/volume can be used to filter and select the compound libraries.
Keywords: ErbB Receptors; simulace molekulového dockingu; Humans; vazebná místa; Binding Sites; Protein Kinase Inhibitors; inhibitory proteinkinas; Decision Making; Molecular Docking Simulation; mutace; lidé; ligandy; Ligands; Drug Design; rozhodování; Mutation; erbB receptory; racionální návrh léčiv